SoCManager: uma ferramenta de apoio ao gerenciamento de configuração de software - Cunha, João Ronaldo Del-ducca (Universidade Federal de São Carlos, 2005)
The processes of Software development contribute to the success of software projects by means of the execution of activities that contribute to the fulfillment of the deadlines and the requirements agreed with the customer. The Software Configuration Management (SCM) process, for instance, defines activities for Identification, Control, Status Management and Configuration Audit, that contribute for the rise and leverage of the quality of the project through the control of the produced artifacts and the assistance to the other processes especially maintenance. However, there are still many software companies which yet have not implemented the SCM process, due to the difficulties in turning the execution of this this process in something actually operational. These difficulties include the lack of a policy to the implementation of SCM process and the lack of tools that support SCM activities. In this context and searching to take care of the needs of software companies in improving the quality of its projects, this research project was developed with the objective of assisting the implementation of the SCM process, in software companies. So this research it was divided in three parts: a) an approach for the implementation of a SCM process in software companies; b) a proposal of an approach for the SCM process, which defines the agents and activities inside the process; and c) the implementation of a tool to support the SCM process approach proposed in this research.
Keywords: Engenharia de software; Qualidade de software; Melhoria de processo; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO